Effect of curing methods during a long time gap between two printing sessions on the interlayer bonding of 3D printed cementitious materials. (16th May 2022) - Chen, Yu; Chang, Ze; He, Shan; Çopuroğlu, Oğuzhan; Šavija, Branko; Schlangen, Erik
Highlights: Influences of curing methods on the interlayer bonding of 3D printed cementitious materials for a long time gap were studied. The printed 2-layer samples were tested in the uniaxial tension under fixed boundary conditions. Air void features of various printed specimens were characterized. An inverse 2D lattice model was employed to quantify the local mechanical strength of cementitious matrix in the interlayer zone of different printed specimens. The microstructure of the interlayer zone was observed under an ESEM. Abstract: A good bond between the layers of 3D printed cementitious materials is a prerequisite for having high structural rigidity for the printed elements. However, the influence of printing process on an interlayer bond is still not well understood. This study investigates the influence of curing methods (i.e., air curing, plastic film covering, wet towel covering and water mist-30 min/-60 min) on the interlayer bonding characteristics of 3D printed cementitious materials for a long time interval between two printing sessions. Results showed that the interlayer bonding could be improved by covering the substrate with a plastic film or a wet towel. However, applying water mist every 60 min/30 min on the deposited layer was detrimental to the interlayer bonding. Furthermore, the interlayer bond strength of studied specimens appeared to be dominated by the mechanical strength of the cementitious matrix at the interface rather than its air void structure. Therefore, covering unfinished printed elements with plastic film or wet towels can be a practical solution to maintain a sufficiently humid environment during long waiting periods, which is vital for its interlayer adhesion.